Pengaruh Sosial Media Terhadap Komunikasi Interpersonal dan Cyberbullying Pada Remaja - Vydia, Vensy; Irliana, Nursanti; Savitri, Anna Dian (Jurnal Transformatika, 2014)
Internet provides any information which could help teenagers in many cases, including to communicate with their friends. On the other way, internet technology which makes communication easier, does some negative effects related with interpersonal communication. Teenagers are not willing to do direct communication, including with their families. The purpose of this research is to find out and to prove whether social media impacts to interpersonal communication and cyberbullying of   teenagers . Further, this research is giving some solutions for teenagers to hpersonal communication altough they are social media addicted. The subject of this research is 500 students in age of 16 up to 19 years old.